The improvement trajectory of PCR DNA replication and ERP software as general purpose technologies: an exploratory study of 'anchor technologies'. Issue 3 (15th March 2016) - Lehrer, Mark; Banerjee, Preeta M.; Wang, I. Kim
ABSTRACT: As an effort to peek into the black box of large-scale general purpose technologies (GPTs) like biotechnology and information technology, we develop the concept of 'anchor technologies'. An anchor technology is a core technology of a large-scale GPT ('mega-GPT') that opens a new era in the development and diffusion of the mega-GPT. We trace the historical evolution of two process-based, yet otherwise very different, anchor technologies: enterprise resource planning (ERP) software within the mega-GPT of information technology and polymerase chain reaction (PCR) DNA replication within the mega-GPT of biotechnology. The case studies reveal the utility of 'productisation' as an important means of commercialising innovations in anchor technologies; more generally, the interplay between improvement in process-based technologies and in complementary product-based technologies provides insight into how ERP and PCR were able to sustain a path of continued improvement within their respective mega-GPT.